2010
DOI: 10.1038/nature09553
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of an amygdala microcircuit that gates conditioned fear

Abstract: The role of different amygdala nuclei (neuroanatomical subdivisions) in processing Pavlovian conditioned fear has been studied extensively, but the function of the heterogeneous neuronal subtypes within these nuclei remains poorly understood. We used molecular genetic approaches to map the functional connectivity of a subpopulation of GABAergic neurons, located in the lateral subdivision of the central amygdala (CEl), which express protein kinase C-delta (PKCδ). Channelrhodopsin-2 assisted circuit mapping in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
953
4
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 775 publications
(1,027 citation statements)
references
References 53 publications
61
953
4
9
Order By: Relevance
“…Others have shown that stimulating channelrhodopsinexpressing BLA terminals in the CeA produced an anxiolytic effect (Tye et al, 2011). The CeA is known to mediate conditioned fear and the acquisition of fear conditioning via inhibitory circuitry Haubensak et al, 2010;Wilensky et al, 2006). It is possible that ubiquitous expression of our construct was not sufficient to yield an obvious behavioral phenotype and may have affected the microcircuitry within the CeA itself.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that stimulating channelrhodopsinexpressing BLA terminals in the CeA produced an anxiolytic effect (Tye et al, 2011). The CeA is known to mediate conditioned fear and the acquisition of fear conditioning via inhibitory circuitry Haubensak et al, 2010;Wilensky et al, 2006). It is possible that ubiquitous expression of our construct was not sufficient to yield an obvious behavioral phenotype and may have affected the microcircuitry within the CeA itself.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the hyperactivity seen in the PL and BA when extinction was poor (i.e., immediate), this suggests a complex network that extends from distinct mPFC populations to these very specific amygdala populations in mitigating the effect of extinction recency. However, more work is needed to determine the specificity of these microcircuits as the cell-type (PKCd+/2; glutamate/GABAergic receptor subtypes) and the precise afferents/efferents of these amygdala subregions are critically important in regulating fear expression and extinction Haubensak et al 2010;Dobi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, BLA neurons project to the lateral subdivision of the central amygdala, which sends GABAergic projections to the medial subdivision of the central amygdala (Haubensak et al, 2010). The fear response (ie, freezing) is controlled by projections from medial subdivision of the central amygdala to the periaqueductal grey (Fanselow, 1991).…”
Section: Neural Systems Involved In Fear Learningmentioning
confidence: 99%